2010
DOI: 10.1177/0038038510381616
|View full text |Cite
|
Sign up to set email alerts
|

Out of Sight, Out of Mind: Family Resemblances in Lesbian Donor Conception

Abstract: A B S T R AC TFamily resemblances and connectedness constitute a recent interest in sociological debate. This article seeks to build on and expand this debate by empirically exploring the meaning of physical family resemblances in the context of lesbian donor conception. This constitutes a neglected area as previous studies primarily explore gamete donation and physical resemblances in the context of heterosexual assisted conception. Considerably less attention has been paid to the specific dynamics inherent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 18 publications
1
52
0
5
Order By: Relevance
“…The literature acknowledges that less attention has been paid to the specific dynamics inherent in lesbian donor conception, and how lesbian couples navigate these processes (Nordqvist 2010(Nordqvist , 2012. However, with respect to sperm donation decisions and sexual preference, research has shown that the only major difference being "that heterosexual women begin DI attempts on average at an older age" (Leiblum et al 1995 pg 11).…”
Section: Limitationsmentioning
confidence: 99%
“…The literature acknowledges that less attention has been paid to the specific dynamics inherent in lesbian donor conception, and how lesbian couples navigate these processes (Nordqvist 2010(Nordqvist , 2012. However, with respect to sperm donation decisions and sexual preference, research has shown that the only major difference being "that heterosexual women begin DI attempts on average at an older age" (Leiblum et al 1995 pg 11).…”
Section: Limitationsmentioning
confidence: 99%
“…Os traços imaginados para o bebê eram sempre características físicas que eram "puxadas" de suas famílias e das de seus maridos. Se a semelhança física pode ser considerada um modo de visualizar conexões entre as pessoas (Carsten 2000b;Cussins 1998;Nordqvist 2010), sua projeção parecia também criar continuidade entre o bebê, seus pais e suas redes de parentesco.…”
Section: "Deus Não Dá Tudo"unclassified
“…Assim, a continuidade com as gerações anteriores era sempre imaginada, mas colocava-se como distinta, recebendo acentuações diversas. Portanto, busco problematizar a relação entre semelhança física e descendência, como outros autores (Cannell 2011;Carsten 2000b;Cussins 1998;Nordqvist 2010), mostrando que as distinções de classe social, raça e etnicidade presentes na sociedade brasileira são mobilizadas juntamente com os pesos ontológicos dos laços de parentesco no processo de construir vínculos para o bebê.…”
unclassified
See 1 more Smart Citation
“…Rather resemblances 'speak of the potential for affinity' (Mason, 2008: 34). Therefore talking about resemblances becomes a resource to affirm connectedness or indeed distance (Becker et al, 2005, Nordqvist, 2010, Roberts 2012b) and therefore may also be a family But me and my sister and my mum and all that side we're all really alike aren't we? Must have strong genes or something because we all… like my sister's little girl looks like she's mine.…”
Section: Talking About Resemblancementioning
confidence: 99%